Multiplexed DNA detection using a gold nanorod‐based fluorescence resonance energy transfer technique. (10th March 2015) - Wu, Qiang; He, Yanlong; Tian, Jianniao; Zhang, Juanni; Hu, Kun; Zhao, Yanchun; Zhao, Shulin
Abstract: A fluorescence resonance energy transfer method for multiplex detection DNA based on gold nanorods had been successfully constructed. This method is simple, easy to operate, good selectivity, no requirement to label the probe molecule and can analyze simultaneously multiple targets of DNA in one sample. The limit of detection for the 18‐mer, 27‐mer and 30‐mer targets is 0.72, 1.0 and 0.43 nM at a signal‐to‐noise ratio of 3. The recoveries of three targets were 96.57–98.07%, 99.12–100.04% and 97.29–99.93%, respectively. The results show that the method can be used to analyze a clinical sample or a biological sample; it also can be used to develop new probes for rapid, sensitive and highly selective multiplex detection of analytes in real samples. Copyright © 2015 John Wiley & Sons, Ltd.